Analysis of Cytoplasmic and Secreted Proteins of Staphylococcus aureus Revealed Adaptive Metabolic Homeostasis in Response to Changes in the Environmental Conditions Representative of the Human Wound Site - Mousa M. Alreshidi; R. Hugh Dunstan; Margaret M. Macdonald; Vineet K. Singh; Tim K. Roberts (Microorganisms, 2020)
The pathogenesis of Staphylococcus aureus is mainly attributed to its capability to adjust to changes in environmental conditions, including those present on human skin or within a wound site. This study investigated the changes in the cytoplasmic and secreted proteins in S. aureus that occurred in response to alterations in the environmental parameters that could be found in the human wound site. In total, sixty differentially regulated cytoplasmic proteins were detected using a label-free quantification approach, and these proteins were classified into ten molecular functions: protein biosynthesis, glycolysis, signal transduction, metabolism, cell cycle, transport, energy generation, cell anchorage, nucleotide biosynthesis and unknown. These changes represented characteristic protein profiles when evaluated by principal component analysis. The bacterium responded to elevated NaCl at pH 6 by decreasing the abundance of the majority of cytoplasmic proteins, while at pH 8 there was an increase in the levels of cytoplasmic proteins in comparison to the untreated cells. The analysis of the secreted proteins showed that there was a high degree of difference in both the intensity and the distribution of many individual protein bands in response to environmental challenges. From these results, it was deduced that specific metabolic homeostasis occurred under each combination of defined environmental conditions.